The Effect Of Green Accounting,And Environmental, Social, and Governance on Firm Value With Firm Size as a Moderating Variable - Dewi Nidia Soepriadi; Christina Sososutiksno; Paul Usmany (LP2M IAIN Palopo, 2026)
This study aims to empirically examine the effect of Green Accounting and Environmental, Social, and Governance (ESG) on Firm Value, with Firm Size as a moderating variable, in mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The population in this study was all mining companies listed on the IDX, with a sampling technique resulting in 32 observational samples. The data analysis method used was Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results of the study indicate that Green Accounting does not have a significant effect on Firm Value with a significance value of 0.951. Conversely, ESG was found to have a positive effect on Firm Value at a significance level of 10% with a value of 0.080. Regarding the moderating role, Firm Size was unable to moderate the effect of Green Accounting on Firm Value (significance value of 0.965). However, Firm Size was proven to moderate the effect of ESG on Firm Value with a negative (weakening) relationship direction at a significance level of 10% (significance value of 0.085). The results of the analysis also show that Firm Size acts as a Quasi Moderator (Pseudo Moderator) in this research model. Simultaneously, this model has a significance value of 0.014 with the ability to explain variations in Firm Value of 26.4% (Adjusted R Square)